A new approach to study interaction parameters in cyanobiphenyl liquid crystal binary systems. (January 2015) - Javadian, Soheila; Dalir, Nima; Gilani, Ali Ghanadzadeh; Kakemam, Jamal; Yousefi, Ali
Graphical abstract: Highlights: The phase transition of 7CB and 5CB liquid crystals studied using the DSC. This work includes the determination of the eutectic in the 7CB/5CB mixture. The excess functions and interaction parameters calculated in the 7CB/5CB mixtures. The P ∗ randomicity parameter used to describe the phase transitions of C–N and N–I. A small amount of P ∗ showed a non-random identity of the C–N phase transition. Abstract: The phase transition of heptylcyanobiphenyl 7CB and pentylcyanobiphenyl 5CB liquid crystals was investigated using the differential scanning calorimetry DSC technique. Then, the phase transition of different compositions of 7CB/5CB binary mixture was studied to determine the eutectic point. The phase diagram of mentioned binary system in 7CB mole fraction of 0.45 at T = 273.45 K is in good agreement with that of predicted from Schroder–van Laar equation. The thermodynamic excess functions and interaction parameters were calculated to describe the phase transition physically using the non-random mixing for the first time. The P ∗ randomicity parameter was used to describe the phase transitions of C–N and N–I in which a small amount of P ∗ shows a non-random identity of C–N phase transition. Contrarily, the P ∗ is greater in N–I phase transition showing a random mixing process.